Profesionalisme Aparatur dalam Pelayanan Publik Di Bidang Kebencanaan – BPBD Kota Palu - Taufik, Agrit; Ramadani, Haerul; Setiawan, Moh Panca Putra; Dikirna. E, Teuku Syabila; Jaya, Moh Resky Indra (Sekolah Tinggi Ilmu Administrasi (STIA) Pembangunan Palu, 2025)
This study examines the professionalism of disaster management personnel and the quality of public disaster services provided by the Regional Disaster Management Agency (BPBD) of Palu City by applying the SERVQUAL model developed by Parasuraman, Zeithaml, and Berry. As a disaster-prone region affected by earthquakes, tsunamis, flash floods, and extreme weather, Palu requires a highly responsive, reliable, and competent disaster response system. This research uses a qualitative descriptive approach to understand how BPBD personnel implement disaster management services through the five SERVQUAL dimensions: tangibles, reliability, responsiveness, assurance, and empathy. Data were collected through in-depth interviews, observations, and documentation studies.The findings reveal that BPBD Palu has demonstrated strong tangible aspects, reflected in the availability of disaster response equipment such as flood pumps, high-capacity lighting machines, and emergency operational tools that support effective fieldwork. Reliability is evident in their consistent disaster response procedures and the use of community satisfaction indices to evaluate service outcomes. Responsiveness is strengthened by multilayered communication systems, including Starlink satellite technology, GSM-based radio communication, and point-to-point networks, ensuring uninterrupted coordination during emergencies.In terms of assurance, BPBD personnel show competence and professionalism through the mastery of technical skills, disaster protocols, and the ability to coordinate with various stakeholders such as OPD, police, military, and humanitarian agencies. Empathy is reflected in their humanistic communication approach, emotional support, and psychological assistance for vulnerable groups such as children and women experiencing trauma after a disaster.This study concludes that BPBD Palu has effectively implemented the SERVQUAL dimensions, indicating a high level of professionalism in delivering disaster services. However, continuous capacity building, improved information distribution, and stronger community engagement remain essential to enhance future disaster management performance. The results of this study contribute to strengthening the theoretical and practical understanding of public service quality in the disaster management sector, especially within local governments in high-risk regions like Palu